Conflitos no aproveitamento hídrico superficial na bacia hidrográfica do rio São Marcos, Alto Paranaíba - Soares, Sérgio Siqueira Prado (2019)
Currently in the Brazilian territory several river basins present conflicts of interest between irrigants and the hydroelectric sector due to the use of surface water (ANA, 2017). The optimization of a water resources system is a complex engineering problem, requiring the mathematical formulation linked to computational algorithms in order to describe the dynamics of the natural system. The objective of this work was to optimize the surface water use in the São Marcos river basin, minimizing the conflicts of water use between the Batalha and Serra do Facão Hydroelectric Plants and the irrigation through central pivots. This basin is located in the central-western region of the Brazilian territory, whose main watercourse is tributary of the Paranaíba river on its right bank. The mathematical simulations were performed with the aid of the computational tool AQUATOOL, which acts as a decision support system for water resources in a watershed scale. Within the tool the optimization module OPTIGES was used. Due to the limitation of fluviometric and climatological data in the basin, the simulations were performed from October 2014 to September 2017. Different grant criteria were simulated from those currently adopted by the States of Minas Gerais and Goiás, with higher and lower percentages than the flow. maximum allowable on an annual basis, in addition to comparing the current criteria with reference flows determined on a seasonal basis (six driest and six wettest months). In the study of water availability it was found that the substitution of the current grant criteria (50% of Q7,10 in Minas Gerais and 70% of Q95 in Goiás State) to 30% of Q7,10 was the one that brought the worst results. where more than 27% of the entire basin area exceeded the maximum allowable limits. The best situation was found using the criteria 80% of Q7,10 and 70% of Q95, where 2.3% and 5.5%, respectively, were the areas above the grantable limits. For the change of reference flows calculated on seasonal basis, a worsening of water availability was observed when using the drought period, increasing the critical area by 8% when compared to the annual base (approximately 1,000 km²). For the rainy season, the improvement in water availability was only 2% over the annual basis. In regions where scarcity situations are more frequent, priority levels were considered for each type of demand, focusing mainly on irrigation, electricity generation and maintenance of minimum residual (or ecological) flow in each stretch of the São Marcos. Upstream of the Batalha reservoir, maximum cut-offs in the volume captured for irrigation demands reached 89%, focusing on maintaining ecological flow and generating hydroelectric power. In this context, the study will technically assist decision-making in this basin. as well as contributing to the theme of new grant criteria.